2017
DOI: 10.25260/ea.17.27.3.0.488
|View full text |Cite
|
Sign up to set email alerts
|

Diversidad de micobiota en diferentes especies de hormigas cortadoras de hojas y sitios de Argentina

Abstract: A�������. A�ine ants are a monophyletic group comprising more than 230 species, distributed exclusively in the New World. All higher A�ini ants depend on the cultivation of fungus gardens for food, and those gardens are continuously exposed to alien microorganisms. The present work describes, for the first time, the composition, relative frequency and the richness of the fungal species comprising the mycobiota from the garden of the most abundant Acromyrmex species from different regions of Argentina. We also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…Our results showed that the biological control of LCA can be achieved after several applications made over a relatively long period of time. A 60% control, as achieved in this study, would represent a significant reduction in crop/tree herbivory with its concomitant economic benefit; and, on the other hand, maintaining some colonies of LCA alive would contribute natural enemies such as parasitoid phorid flies (Folgarait, 2013; Elizalde et al., 2018), and generalist pathogens (Goffré & Folgarait, 2017; Marfetán & Folgarait, 2017) or specialist pathogens (Augustin et al., 2013; Marfetán et al., 2018), that could help reduce the uncontrolled colonies (Currie et al., 2003; Guillade & Folgarait, 2014b; Bizarria et al., 2018). Our results contrast in efficiency with the only other long‐term biological control assessment published so far, which reported 100% control of five A. cephalotes colonies over 37 weeks with three applications of M. anisopliae and T. viride (Lopez & Orduz, 2003).…”
Section: Discussionmentioning
confidence: 69%
“…Our results showed that the biological control of LCA can be achieved after several applications made over a relatively long period of time. A 60% control, as achieved in this study, would represent a significant reduction in crop/tree herbivory with its concomitant economic benefit; and, on the other hand, maintaining some colonies of LCA alive would contribute natural enemies such as parasitoid phorid flies (Folgarait, 2013; Elizalde et al., 2018), and generalist pathogens (Goffré & Folgarait, 2017; Marfetán & Folgarait, 2017) or specialist pathogens (Augustin et al., 2013; Marfetán et al., 2018), that could help reduce the uncontrolled colonies (Currie et al., 2003; Guillade & Folgarait, 2014b; Bizarria et al., 2018). Our results contrast in efficiency with the only other long‐term biological control assessment published so far, which reported 100% control of five A. cephalotes colonies over 37 weeks with three applications of M. anisopliae and T. viride (Lopez & Orduz, 2003).…”
Section: Discussionmentioning
confidence: 69%
“…(2016) ; Li et al. (2016) ; Marfetán (2016) ; Barcoto et al. (2017) ; Canali (2017) ; do Nascimento et al.…”
Section: Methodsmentioning
confidence: 99%